Prognosis and prognostic factors for patients with chronic myeloid leukemia: Nontransplant therapy - Hasford, Joerg; Pfirrmann, M.; Hehlmann, Rüdiger; Baccarani, M.; Guilhot, F.; Mahon, F. X.; Kluin-Nelemans, H. C.; Ohnishi, K.; Thaler, J.; Steegmann, J. L. (Seminars in hematology, 2003)
Reliable knowledge about an individual's prognosis is needed to select the appropriate treatment for patients with chronic myeloid leukemia (CML). The New CML score using age, spleen size, blast cell count, eosinophil count, basophil count, and platelet count shows good discrimination for survival (96, 65, or 42 months, P ≤ .0001) and has been thoroughly validated. Careful analyses indicate that the New CML score is considerably more precise in identifying high-risk patients than the Sokal score. Achievement of complete hematologic response (CHR) up to 9 months shows a distinct impact on survival, which, however, depends on the baseline prognosis. Ten-year survival probabilities for low- and intermediate-risk patients with a CHR were 0.51 (95% confidence interval [CI], 0.42 to 0.60) and 0.23 (95% CI, 0.15 to 0.31) and without a CHR were 0.26 (95% CI, 0.16 to 0.37) and 0.12 (95% CI, 0.04 to 0.20). In high-risk patients CHR had no impact on prognosis. Therapeutic options were widened by the approval of imatinib for the treatment of CML. However, it will still take 2 or more years to know whether the high rates of CHR and cytogenetic complete remission (CCR) achieved with imatinib translate into a clinically relevant survival advantage for all patients.